2021
DOI: 10.3390/s21248369
|View full text |Cite
|
Sign up to set email alerts
|

Posture Detection of Individual Pigs Based on Lightweight Convolution Neural Networks and Efficient Channel-Wise Attention

Abstract: In this paper, a lightweight channel-wise attention model is proposed for the real-time detection of five representative pig postures: standing, lying on the belly, lying on the side, sitting, and mounting. An optimized compressed block with symmetrical structure is proposed based on model structure and parameter statistics, and the efficient channel attention modules are considered as a channel-wise mechanism to improve the model architecture.The results show that the algorithm’s average precision in detectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…This review includes articles with Qualsyst score percentages ≥60%. As a result, 23 articles were included for in-depth analysis [ 7 , 13 , 14 , 15 , 16 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]; the remaining 5 articles were excluded since their score was below the acceptance percentage [ 45 , 46 , 47 , 48 , 49 ]. The flow diagram of the review phases’ is shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This review includes articles with Qualsyst score percentages ≥60%. As a result, 23 articles were included for in-depth analysis [ 7 , 13 , 14 , 15 , 16 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]; the remaining 5 articles were excluded since their score was below the acceptance percentage [ 45 , 46 , 47 , 48 , 49 ]. The flow diagram of the review phases’ is shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The first study identified dates back to 2016 [ 39 ], and 95.7% (22/23) of the studies were conducted in the last five years (2018–2022). Most of the 23 studies were conducted in Europe (11/23, 47.8%) [ 7 , 15 , 16 , 29 , 30 , 32 , 33 , 38 , 39 , 40 , 41 ] followed by Asia (8/23, 34.7%) [ 13 , 27 , 34 , 35 , 36 , 42 , 43 , 44 ], and Oceania (3/23, 13%) [ 31 , 37 , 44 ]. An overview of the results is presented in Table 2 , and a detailed analysis of the selected studies are displayed in Table 3 , Table 4 and Table 5 , according to sensor fusion level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the significant advancement of Internet of things (IoT) and artificial intelligence (AI), Fourth Industrial Revolution DOI: 10.1002/adsr.202200072 (Industry 4.0) is revolutionizing the way that companies upgrade and transform manufacturing technologies to realize smart digital factories. [1][2][3][4][5] Automatic machines and robotics play a vital role in our daily lives and are essential components for manufacturers, which leverage AI to finish cloud computing and data analytics in their production facilities and throughout their operations. [6][7][8][9] The fast development of AI started from 2012 benefiting from the improvement of computation power and speed, in which graphics processing unit (GPU) accelerates the design of various deep learning algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Although deep-learning algorithms [ 11 , 12 , 13 ] have developed rapidly, they require a large number of calculations and numerous parameters, and models can normally only run on high-performance workstations equipped with graphics processing units (GPUs). A computer-vision technology based on lightweight deep learning [ 14 , 15 , 16 ] has emerged owing to cost considerations. This paper proposes a lightweight deep learning-based approach for the early warning and supervision of sow behaviors preceding and during farrowing.…”
Section: Introductionmentioning
confidence: 99%